Sintesis 2,5-bis(4-hidroksibensilidin) siklopentanon dari p-hidroksibenzaldehid dan Siklopentanon dengan Katalis Asam Sulfat - Murtisiwi, Lusia; Lusia Murtisiwi (Jurnal Farmasi (Journal of Pharmacy), 2012)
2,5-bis(4-hydroxybenzilidene)cyclopentanone is one of curcumin analog compound. The aim of this research is to synthesize 2,5-bis(4-hydroxybenzilidene)cyclopentanone               from              p- hydroxybenzaldehyde and cyclopentanone using sulfuric acid as a catalyst. Persumably, sulfuric acid, a diprotic acid can be used as a catalyst in synthesizing 2,5-bis(4-hydroxybenzilidene)cyclopentanone. The The research could be clasified as the descriptive explorative non-analytic research with the succedd of synthesizing of 2,5-bis(4- hydroxybenzilidene)-cyclopentanone as the parameter. The research was done by reacting 0,06 mol p-hydroxybenzaldehyde and 0,03 mol cyclopentanone in methanol solution with sulfuric acid as a catalyst. The analysis was occupied with two ways, they were qualitative and quantitative. The qualitative analysis was done in a series of test. They were organoleptic test, solubility test, thin layer chromatography (TLC) test, melting point estimation, elucidation of synthesized compound with infra red (IR) spectroscopy, proton nuclear magnetic resonance (1H-NMR) and carbon-13 nuclear magnetic resonance (13C-NMR) spectroscopy. The quantitative analysis was done by estimating the yield of synthesized compound. The research result showed that synthesized compound was a yellowish powder, specified odor, tasteless but it has specified effect on tongue. The melting point of synthesized compound was more than 300˚C. The TLC test showed that synthesized compound has an Rf as much as 0,73 which was different with p-hydroxybenzaldehyde that was 0,84. The IR, 1H-NMR and 13C-NMR spectra showed that the synthesized compound was 2,5-bis(4-hydroxybenzilidene)- cyclopentanone with yield for about 10,64%.